Квест: художественная лит-ра / Б. Акунин - Акунин Борис (Жанры, 2009)
Экземпляры: аб (ретроконверсия) / Инвентарный номер: 44432 / Цена: 260.40 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: А 44 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6